Profile of Social Support on The Quality of Life of People With HIV/AIDS (PLWHA) - Susmiati Susmiati; Indah Jayani (Universitas STRADA Indonesia, 2020)
The purpose of this research is to know the relationship between social support and quality of life for PLWHA. This research is a correlational analytic study that is quantitative using a cross sectional approach. The samples was 32 people who were selected by the purpossive sampling technique. The research instruments used were SSQ and WHOQOL-HIV BREF. The results of data analysis using the Spearman rank test showed that the value of ρ value = 0,000 <α = 0.05. The research result states a relationship between social support and quality of life for PLWHA. Based on this research, it is expected that PLWHA can open themselves to the surrounding environment in order to get high social support so that it can improve the quality of life.